COMPARISON OF EFFICACY OF METFORMIN ALONE AND METFORMIN+ GLIBENCLAMIDE IN GESTATIONAL DIABETES MELLITUS (Journal of Medical & Health Sciences Review, 2025)
Introduction: Gestational diabetes mellitus (GDM) is associated with significant maternal and neonatal complications if inadequately treated. While insulin remains the gold standard for pharmacological management, hypoglycemic agents such as metformin and glibenclamide are increasingly considered due to promising results.Objective: To compare the frequency of treatment failure between metformin monotherapy and a combination of metformin plus glibenclamide in the management of GDM.Methods: This randomized controlled trial included 160 pregnant women with GDM at ≥28 weeks gestation. Participants were randomized into two groups: Group A received metformin alone, while Group B received metformin combined with glibenclamide. Glycemic control was evaluated after two weeks. Treatment failure was defined as persistently elevated glucose levels requiring insulin.Results: Combination therapy significantly reduced treatment failure (12.5%) compared to metformin alone (41.3%) (p = 0.00004). Glycemic control was shown in 88% patients of the combination group versus 59% in the metformin group. The efficacy of combination therapy was consistent across all BMI categories.Conclusion: The addition of glibenclamide to metformin significantly improves glycemic control and reduces treatment failure in GDM patients, offering a viable alternative in resource-constrained settings.